Estimation of Hazard Rate and Mean Residual Life Ordering for Fuzzy Random Variable - S. Ramasubramanian; P. Mahendran (Abstract and Applied Analysis)
L2-metric is used to find the distance between triangular fuzzy numbers. The mean and variance of a fuzzy random variable are also determined by this concept. The hazard rate is estimated and its relationship with mean residual life ordering of fuzzy random variable is investigated. Additionally, we have focused on deriving bivariate characterization of hazard rate ordering which explicitly involves pairwise interchange of two fuzzy random variables X and Y.